Influence of Exposure Time on Gene Expression by Human Intestinal Epithelial Cells Exposed to Lactobacillus acidophilus - O'Flaherty, Sarah (American Society for Microbiology, 2012)
Analysis of global temporal gene expression by human intestinal cells when exposed to Lactobacillus acidophilus revealed induction of immune-related pathways and NF-κB target genes after a 1-h exposure, compared to a 4- or 8-h exposure. Additionally, an L. acidophilus derivative expressing covalently bound flagellin resulted in increased induction of il8, cxc1, and cxcl2 compared to the parent L. acidophilus.